Desain Model Sistem Keamanan Berbasis Kamera Dengan Image Enhancement Algorithm - Phie Chyan; Adi Chandra Syarif; Sean Coonery Sumarta; Fransiskus Eduardus Daromes (JURIKOM (Jurnal Riset Komputer), 2018)
Security is a supporting factor in creating order and stability in the social environment. The issue of environmental security is related to efforts made to avoid and overcome criminal acts in society and now thanks to the advancement of information and communication technology, the function of safeguarding and controlling the environment can be supported by the help of technology to facilitate human work. The security system developed is supported by digital image processing software to process snapshot and recorded images from system cameras with the aim of improving the quality of visual images for the sake of analysis and digital forensic evidence that can be used in law enforcement related to criminal acts. The end result is a product innovation security system that can be utilized by the community in various needs related to security and supervision activities.